2018
DOI: 10.1159/000490246
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Serum NGAL and Troponin I against Acute Kidney Injury in Egyptian ICU Patients after Open Heart Surgery: A Pilot Study

Abstract: Background: Acute kidney injury (AKI) is a common complication following cardiac surgery and percutaneous coronary interventions, with an estimated incidence rate around 30%, depicted by long-term intensive care unit stay and culminating renal dysfunction over time, triggering either perpetual renal damage evolving to chronic kidney disease/end-stage renal disease transitions or high vulnerability for sudden death after surgery. The classical diagnosis of AKI is based on a sharp rise in serum creatinine that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Our data revealed that NGAL values were significantly higher in patients who developed AKI than in those without AKI. Mosa 8 did a similar study in patients of open heart surgery and found that baseline serum NGAL values were higher in the AKI group compared to the non-AKI group ( p < 0.01). Haase-Fielitz et al 9 found similar performance of NGAL in patients of cardiac surgery.…”
Section: Discussionmentioning
confidence: 88%
“…Our data revealed that NGAL values were significantly higher in patients who developed AKI than in those without AKI. Mosa 8 did a similar study in patients of open heart surgery and found that baseline serum NGAL values were higher in the AKI group compared to the non-AKI group ( p < 0.01). Haase-Fielitz et al 9 found similar performance of NGAL in patients of cardiac surgery.…”
Section: Discussionmentioning
confidence: 88%
“…The early increase of BTP and CysC might reflect already some degree of kidney dysfunction prior to surgery, possibly induced by the medical condition necessitating the surgery. The absence of pre-op rise in sCr can be explained by tubular excretion of sCr when GFR decreases [1,5,7,[13][14][15]. The absence of pre-op rise in NGAL levels in both groups is puzzling, as other groups observed an increase in NGAL 12-24 h before a rise in sCr in AKI [5,7,8,[11][12][13][14][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of pre-op rise in sCr can be explained by tubular excretion of sCr when GFR decreases [1, 5, 7, 13-15]. The absence of pre-op rise in NGAL levels in both groups is puzzling, as other groups observed an increase in NGAL 12–24 h before a rise in sCr in AKI [5, 7, 8, 11-14, 17-20]. Different explanations may underly this observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations